2022
DOI: 10.1029/2022ef002687
|View full text |Cite
|
Sign up to set email alerts
|

The Future Climate and Air Quality Response From Different Near‐Term Climate Forcer, Climate, and Land‐Use Scenarios Using UKESM1

Abstract: Near‐term climate forcers (NTCFs) can influence climate via interaction with the Earth's radiative balance and include both aerosols and trace gas constituents of the atmosphere (such as methane and ozone). Two of the principal NTCFs, aerosols (particulate matter) and tropospheric ozone (O3), can also affect local air quality when present in the lower levels of the atmosphere. Previous studies have shown that mitigation of NTCFs has the potential to improve air quality and reduce the rate of surface warming in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 73 publications
(154 reference statements)
0
19
0
Order By: Relevance
“…The air pollutant data used in this study has been obtained from the CMIP6 data archive which is hosted at the Earth System Grid Federation and is freely available to download from https://esgf-node.llnl.gov/search/cmip6/. A list of the CMIP6 model diagnostics used in this study from each scenario are provided in Table S1 in Supporting Information S1, along with the relevant data citation for each experiment provided in Table S2 in Supporting Information S1 of the companion paper Turnock et al (2022). Additional simulation data relevant to this publication from the non-AerChemMIP experiment ssp370SST-pdEmis is archived on Zenodo at the following location https://doi.org/10.5281/zenodo.5884604.…”
Section: Conflict Of Interestmentioning
confidence: 99%
See 4 more Smart Citations
“…The air pollutant data used in this study has been obtained from the CMIP6 data archive which is hosted at the Earth System Grid Federation and is freely available to download from https://esgf-node.llnl.gov/search/cmip6/. A list of the CMIP6 model diagnostics used in this study from each scenario are provided in Table S1 in Supporting Information S1, along with the relevant data citation for each experiment provided in Table S2 in Supporting Information S1 of the companion paper Turnock et al (2022). Additional simulation data relevant to this publication from the non-AerChemMIP experiment ssp370SST-pdEmis is archived on Zenodo at the following location https://doi.org/10.5281/zenodo.5884604.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…A detailed explanation of the model setup, emission scenarios and simulations performed for this study can be found in the companion paper (Turnock et al, 2022), with a brief summary also presented here. We use the fully coupled Earth system model, UKESM1, which contains an interactive stratosphere-troposphere chemistry and aerosol scheme coupled to the physical atmosphere ocean climate model, along with other relevant Earth system components such as a terrestrial carbon and nitrogen cycle coupled to a dynamical vegetation model (Sellar et al, 2019(Sellar et al, , 2020.…”
Section: Model Simulations and Future Scenariosmentioning
confidence: 99%
See 3 more Smart Citations